A CONTRIBUTION TO RESEARCH OF DEGRADATION OF CHARACTERISTICS OF VIBRATION PARAMETERS ON VIBRATION ASPECT OF VEHICLE COMFORT - Demić, Miroslav D.; Diligenski, Djordje M (Journal of Applied Engineering Science, 2012)
Dynamic simulation, based on modeling, has a signifi cant role in vehicle development, especially inthe early stages of design process, when relevant parameters are being defi ned. In praxis it is usuallyassumed that vibration parameters are unchangeable, what is basically wrong. All researchesindicate that vibration parameters degrade in time of vehicle service, consequently leading to avariation of its dynamic characteristics. This paper, based on preliminary research results, attemptsto point out the necessity of taking into consideration this variation in the earliest phases of vehicledesign by its implementation in the vehicle simulation model
Keywords: Vibration comfort; Degradation; Vibration parameters; Vehicle